ANALISIS MINAT MAHASISWA UNIVERSITAS DIPONEGORO TERHADAP PEMANFAATAN PELAYANAN KESEHATAN KLINIK PRATAMA UNDIP - Sri Gama Apriani; Septo Pawelas Arso; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The availability of health services in educational institutions has important role in realizing the goals of educational institutions as fulfillment of student welfare in improving healthy living. Diponegoro University (Undip) is one of the educational institutions that provides health services, namely Klinik Pratama Undip. The study result showed results that during the six months of operation, the number of visits of Klinik Pratama Undip has increased every month, but not many students have utilized the service. The research has a purpose is knowing Diponegoro University college students intention in utilizing the health service Klinik Pratama Undip through perceptions of kind of health service, access to helath service, information on health service and prices of health service.This research uses a quantitative method with a cross sectional approach. Samples are taken from 100 people associate degree and undergraduate of Diponegoro University college students. The results showed 52% stated their intentions and 48% stated their disintentions. Bivariate analysis showed that there is correlation between perceptions of kind of health service (p value 0,047), perception of information on health service (p value 0,000) and perceptions of prices of health service (p value 0,009). While the variables that has no correlation is the perceptions of access to health service (p value 0,466). It is recommended to the Klinik Pratama Undip to optimize the promotion of services through collaboration with campus events and roadshows to each faculty at Diponegoro University.